The Implementation of the Halal Facility Policy in Regional Regulation No. 1 of 2020 on the Organization of Halal Tourism in Gunung Padang Tourism Area - Rahman, Muhammad Iqbal; Malau, Hasbullah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the implementation of halal facility policies based on Regional Regulation No. 1 of 2020 concerning the Organization of Halal Tourism in Padang City, specifically in the Gunung Padang Tourism Area. This study uses a descriptive qualitative approach with Van Meter and Van Horn’s (1975) policy implementation theory as the analytical framework. Data was collected through interviews with the Tourism Department, business stakeholders, and the local community around the tourism area. The findings indicate that the policy implementation is still not optimal due to limitations in human resources, funding, and inter-agency coordination. Public and business stakeholders' awareness of the importance of halal facilities remains low, while tourists' behavior does not fully support the application of halal standards. Social, economic, and political factors also affect the effectiveness of policy implementation. Strategies to enhance resource capacity, continuous socialization, and the application of good governance principles are needed to strengthen policy success. This study is expected to provide insights for local governments in realizing a competitive and sustainable halal tourism destination in Padang City.